UHPLC–MS/MS bioanalysis of human plasma coproporphyrins as potential biomarkers for organic anion-transporting polypeptide-mediated drug interactions. (11th May 2018) - Kandoussi, Hamza; Zeng, Jianing; Shah, Kumar; Paterson, Patricia; Santockyte, Rasa; Kadiyala, Pathanjali; Shen, Hong; Shipkova, Petia; Langish, Robert; Burrrell, Richard; Easter, John; Mariannino, Thomas; et al.
Aim: Coproporphyrins (CP-I and CP-III) have been identified as possible biomarkers to predict human hepatic organic anion-transporting polypeptides-mediated-drug-interactions for a new drug entering clinical development.Results: The method is applicable to quantify plasma CP-I and CP-III within 0.078–15.0 nM. The results identify and address a number of challenges encountered with porphyrin assays such as photodegradation and interferences. To overcome interferences from ubiquitous porphyrins, a surrogate matrix was used to prepare calibration standards. Quality controls were prepared in plasma and surrogate matrix to ensure parallelism between surrogate matrix and plasma.Conclusion: A robust UHPLC–MS/MS assay was developed and validated for CP-I and CP-III in plasma, and is currently applied to clinical studies to confirm suitability of Coproporphyrins as a potential substitute for drug–drug interaction study.